Estudo da aeração e agitação na produção de celulases por Trichoderma Koningii - Santos, Patricia Alves dos (2023)
Cellulases are enzymes capable of hydrolyzing cellulose, the most abundant biopolymer in nature. Currently, the alcohol industry has been paying special attention to cellulases, as the hydrolysis of cellulose results in sugars that can be fermented into second-generation ethanol. However, the cost of cellulase production in the bioethanol production process can represent around 40% of the total cost. Therefore, it becomes imperative to seek alternatives to make the cost of cellulase production more viable.In enzymatic production, it is possible to investigate different substrates as well as operational conditions that maximize enzymatic production. The objective of this work was to select a substrate (sugarcane bagasse, wheat bran, coconut fiber, coffee powder, sugarcane bagasse + wheat bran) in a shaker that maximizes cellulase production from the fungus Trichoderma koningii. After optimizing this medium in a bioreactor by changing different agitation conditions (200 and 400 rpm) and aeration rates (0.5 and 1.5 vvm), and consequently finding the volumetric oxygen transfer coefficient (KLa), as oxygen is important in the cellulase production process. Subsequently, partial purification/concentration was carried out by fractionated precipitation with ammonium sulfate and organic solvent.The results show that coffee powder is the substrate that presented the maximum enzymatic activity (0.182 ± 0.034 UI/mL) in 72 hours of submerged cultivation in a shaker. In the bioreactor using coffee powder, the maximum enzymatic production was obtained under the conditions of 200 rpm and 1.5 vvm (0.392±0.004 UI/mL). The KLa values increase with the increase in agitation and aeration, reaching the maximum KLa value of 350.26 h-1. However, this increase did not interfere with cellulase production. In the partial purification process by fractionated precipitation with ammonium sulfate, a maximum yield of 10.69% and a purification factor of 1.78 were obtained. Regarding the purification step with organic solvent, the maximum yield achieved was 35.68% with a purification factor of 2.34